Capital Structure, Financial Performance, Investment Decision and Firm Value - Liong, Harlina; Uluputty, Nurdjana Fadjrin (Universitas Pamulang, 2024)
This study aims to determine the effect of Capital Structure, Financial Performance, and Investment Decisions on Firm Value. Capital Structure is measured using the Debt to Equity Ratio (DER), Financial Performance is measured using Return On Assets (ROA), and Investment Decisions are measured using the Price Earning Ratio (PER). Meanwhile, firm value is measured using Tobin's Q. The population in this study are all infrastructure sector companies listed on the Indonesia Stock Exchange for the 2017-2021 period. The number of samples in this study was 9 companies obtained through purposive sampling, and sample data as much as 45 was obtained. This study's data type is secondary data with quantitative research methods. The analysis technique used is panel data regression analysis with a significance level of 5%. This research was processed using Eviews 9 software. It showed that (1) Capital Structure has a significant effect on Firm Value, (2) Financial Performance has a significant effect on Firm Value, and (3) Investment Decisions have a significant effect on Firm Value.